Synthesis, characterization and photocatalytic activity of pristine and doped ZnO (Mn, Fe, Ag and Ni) nanomaterial / Ahmad Khairul Azfar Darman - Darman, Ahmad Khairul Azfar (2021)
Pristine and doped ZnO (Mn-, Fe-, Ag- and Ni) nanomaterial were successfully synthesized by a simplified sol-gel method at different stoichiometry, which are Zn(x)Mn(x-1)O, Zn(x)Fe(x-1)O, Zn(x)Ag(x-1)O and Zn(x)Ni(x-1)O (x = 1 %, 3 %, 5 %, 7 % and 10 %) respectively. In this work, all the nanomaterials were systematically studied based on several factors affecting their performances, which are phase study, morphological study, band gap study, textural properties, and the number of active sites presence on the surface of the nanomaterial using X-ray Diffraction (XRD), Scanning Electron Microscope (SEM), UV-Vis Spectrophotometer, Brunauer-Emmett-Teller (BET) analysis and Temperature Programmed Desorption (TPD – CO2) respectively. This synthesis method of sol-gel was modified by omitting the use of chelating agent to reduce the preparation time obtaining precursor. X-ray Diffraction (XRD) confirmed that the existence of substitutional/pure doping for Mn/ZnO and Fe/ZnO because it depicts the same pattern as pristine ZnO nanomaterial, allowing the dopants ions to substitute in the host’s lattice. Interstitial/impure doping for Ag/ZnO, Ni/ZnO was noted due to the presence of other known crystalline phase known as impurities in which the dopants ions are not slotted into the lattice. Morphological study from (FESEM) showed two significant shapes possessed, which are nanorods and spherical with a variation in diameter and lengthwise. Nanorods which has a smaller diameter compared to spherical will give larger surface area on the surface of nanomaterial. Therefore, condition of synthesis has been accomplished about the nanoscale obtained. Band gap study expressed that all stoichiometry for doped ZnO managed to lower down the wide energy gap value of 3.34 eV pristine ZnO and has a potential for visible light responsive photocatalysis, as well as better photocatalyic activity under UV light irradiation, except 1% Mn/ZnO and 10 % Ni/ZnO because of higher energy gap value at 3.37 eV and 3.35 eV respectively which is mainly due to smaller crystallite size giving rise to apparent separation of energy levels. In terms of the (BET) analysis, the effect of 1 % dopant of Mn/ZnO, Fe/ZnO and Ni/ZnO contributed to a larger surface area with 16.371 m2g-1, 17.457 m2g-1 and 11.970 m2g-1 than that of pristine ZnO (11.671 m2g-1), which supposedly favour photocatalytic activity. Interestingly, amongst all dopants, 5 % Ag/ZnO showed highest photocatalytic activity at 99.93 %, producing at least 14th cycles of nanomaterial reusability on degradation of methyl orange under UV irradiation. This substantial result on nanomaterial reusability has successfully overcomed the problem arose from the synthesis part. The condition of photocatalysis set up was constructed uniformly for all nanomaterials. Larger surface area of 1 % Mn/ZnO, Fe/ZnO and Ni/ZnO nanomaterial showed poor photocatalytic performance at 28.43 %, 73.24 % and 35.68 %. Active sites of nanomaterial is proposed to be an additional factor contributing towards photocatalysis in this work besides band gap, size, morphology and surface area. TPD – CO2 showed that the incorporation of Ag into ZnO lattice has enhanced the number of active sites on the surface of the nanomaterial (166.53 μmol/g) whereas incorporation of Mn/ZnO, Fe/ZnO and Ni/ZnO lowered the number of active sites with respect to pristine ZnO. Active sites measurement is effective and significant, providing opportunities in developing an intensive study as an additional factor. This research work aims to propose and find the key player in photocatalytic performance in which the study is focusing more on the number of active sites present on the surface of nanomaterials. This is because the presence of a larger number of active sites will promote the formation of active radicals.